Karl Marx’s view of the productive forces and its development today (Revista de Investigaciones Universidad del Quindío, 2021)
When studying human society, Karl Marx affirmed that all changes in social life, in the end, originate from the transformation of the productive forces. The development of productive forces is expressed through the conquest of the nature of men. Productive forces reflect the actual capability of men in the process of creating wealth for society and ensuring human development. In any society, in order to create wealth, both workers and means of production are needed. Without instruments for the labor process, men cannot create wealth. That development provides us with more convincing practical evidence to continue affirming Karl Marx’s precise view of the productive forces, and at the same time requires us to supplement and develop his view on this issue inconsistent with reality. In the current context of globalization and the Fourth Industrial Revolution, it is essential to clarify all the practical capabilities used in the production process of the society over the world’s development periods to promote social development. Therefore, this article clarifies the basic arguments to analyze Karl Marx’s view on the productive forces and see the need to refresh and supplement Karl Marx’s theory in the current situation.
Keywords: productive forces; historical materialism; socio-economic form